Establishing a pragmatic framework to optimise health outcomes in heart failure and multimorbidity (ARISE-HF): A multidisciplinary position statement. (1st June 2016) - Stewart, Simon; Riegel, Barbara; Boyd, Cynthia; Ahamed, Yasmin; Thompson, David R.; Burrell, Louise M.; Carrington, Melinda J.; Coats, Andrew; Granger, Bradi B.; Hides, Julie; Weintraub, William S.; Moser, Debra K.; et al.
Abstract: Background: Multimorbidity in heart failure (HF), defined as HF of any aetiology and multiple concurrent conditions that require active management, represents an emerging problem within the ageing HF patient population worldwide. Methods: To inform this position paper, we performed: 1) an initial review of the literature identifying the ten most common conditions, other than hypertension and ischaemic heart disease, complicating the management of HF (anaemia, arrhythmias, cognitive dysfunction, depression, diabetes, musculoskeletal disorders, renal dysfunction, respiratory disease, sleep disorders and thyroid disease) and then 2) a review of the published literature describing the association between HF with each of the ten conditions. From these data we describe a clinical framework, comprising five key steps, to potentially improve historically poor health outcomes in this patient population. Results: We identified five key steps (ARISE-HF) that could potentially improve clinical outcomes if applied in a systematic manner: 1) Acknowledge multimorbidity as a clinical syndrome that is associated with poor health outcomes, 2) Routinely profile (using a standardised protocol — adapted to the local health care system) all patients hospitalised with HF to determine the extent of concurrent multimorbidity, 3) Identify individualised priorities and person-centred goals based on the extent and nature of multimorbidity, 4) Support individualised, home-based, multidisciplinary, case management to supplement standard HF management, and 5) Evaluate health outcomes well beyond acute hospitalisation and encompass all-cause events and a person-centred perspective in affected individuals. Conclusions: We propose ARISE-HF as a framework for improving typically poor health outcomes in those affected by multimorbidity in HF.